Combined steam-dry reforming of toluene in syngas over CaNiRu/Al2O3 catalysts. Issue 4 (16th March 2019) - Oh, Gunung; Park, Seo Yoon; Seo, Myung Won; Ra, Ho Won; Mun, Tae Young; Lee, Jae-Goo; Yoon, Sang Jun
ABSTRACT: Cracking, steam reforming, dry reforming, and combined steam and dry reforming of toluene in model syngas were performed using catalysts to simulate tar removal produced during biomass gasification. The catalysts were prepared by adding Ru, Ca, and Mn to Ni-based catalysts, and their properties were measured using BET, pulse CO chemisorption, XRD and TG. In steam and dry reforming of toluene, a high toluene conversion was observed with increasing Ca content in the catalyst and catalysts containing Ca showed a higher activity than those containing Mn. In combined steam-dry reforming with syngas, 1%CaNiRu/Al2 O3 indicated a conversion of 93.9% at 800°C.